2015
DOI: 10.1159/000438520
|View full text |Cite
|
Sign up to set email alerts
|

Role of MiR-3619-5p in β-Catenin-Mediated Non-Small Cell Lung Cancer Growth and Invasion

Abstract: Background/Aims: The malignancy of non-small cell lung cancer (NSCLC) is largely due to its fast growth and invasion. WNT/β-catenin signaling plays a critical role in regulating NSCLC carcinogenesis. Hence, suppression of β-catenin signal transduction in NSCLC cells may improve the therapeutic outcome. Methods: We analyzed the levels of β-catenin and miR-3619-5p in NSCLC specimens, compared to paired non-tumor normal lung tissue (NT). We did Bioinformatics analyses on the binding sites of 3'-UTR of β-catenin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 27 publications
(25 reference statements)
1
32
0
Order By: Relevance
“…Accumulating evidence has strongly suggested that β-catenin is a crucial factor in various processes of cancer development [31-35]. In our study, we found that β-catenin expression was associated with regional lymph node involvement but not the overall survival.…”
Section: Discussionsupporting
confidence: 39%
“…Accumulating evidence has strongly suggested that β-catenin is a crucial factor in various processes of cancer development [31-35]. In our study, we found that β-catenin expression was associated with regional lymph node involvement but not the overall survival.…”
Section: Discussionsupporting
confidence: 39%
“…A single miRNA can target multiple genes, whereas multiple miRNAs can target a single gene. Recently, miRNA regulatory mechanisms that are dysfunctional in lung cancer have been reported [25-27]. To date, some tumour suppressor miRNAs have been confirmed using cultured cancer cells or animal models of cancer [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs play a significant role in the regulation of cell development, differentiation, proliferation, metastasis, invasion and cell apoptosis [7-14]. Thus, the abnormal alteration of miRNAs could be crucial to the development of diseases including cancers [15-18].…”
Section: Introductionmentioning
confidence: 99%